The Usage of Code Switching in Teaching English at Yayasan Pendidikan Winfield - Cindy Jacinda (ELT (English Language Teaching Prima Journal), 2024)
This research is aimed to find out why the usage of code switching occurs in teaching-learning English. The research was conducted by using qualitative research design. The place of the research is Yayasan Pendidikan Winfield Medan. The subject of the research were 10 students and 2 teachers in Yayasan Pendidikan Winfield Medan. The instrument used in order to collect the data in this research is by in-depth interview and observation. Interview was conducted to the students and the teachers in order to find out why the usage of code switching occurs in teaching-learning English. The result of the finding is that there are 6 students that used intra-sentential code switching, 2 students that used inter-sentential code switching, 2 students that used tag switching, and both of the teachers used intra-sentential code switching. From the data, writer concluded that: (1) most of the subjects of research used intra-sentential code switching; (2) the reason of why students used code switching is that they lack in English vocabulary mastery; (3) the reason of why teachers used code switching is that they want to clarify important point, ease the tension when the class atmosphere become tense.